2014
DOI: 10.1021/ef402286y
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Composition and Fourier Transform Infrared Spectroscopy Analysis of Crude Oils and Their Fractions

Abstract: Detailed compositional analysis of nine crude oils and their saturate, aromatic, resin, and asphaltene fractions were carried out by elemental analysis and Fourier transform infrared spectroscopy. The crude oils had a broad range of physicochemical properties. The largest difference in composition was found in the asphaltene fractions of the oils, followed by the resin fractions. These fractions had significantly higher abundance of oxygen and nitrogen heteroatoms than the saturate and aromatic fractions. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 29 publications
2
36
0
3
Order By: Relevance
“…The band around 1030 cm -1 is generally due to presence of sulfoxide group. [56] Presence of sulfoxide groups in asphaltenes could be due to oxidation. [57] All the asphaltene fractions showed absorbance at this wavenumber with adsorbed fraction showing the highest intensity.…”
Section: Characterization By Ftir Spectrometrymentioning
confidence: 99%
“…The band around 1030 cm -1 is generally due to presence of sulfoxide group. [56] Presence of sulfoxide groups in asphaltenes could be due to oxidation. [57] All the asphaltene fractions showed absorbance at this wavenumber with adsorbed fraction showing the highest intensity.…”
Section: Characterization By Ftir Spectrometrymentioning
confidence: 99%
“…IP do petróleo P01, em relação ao P02, corrobora que este último seria mais susceptível à precipitação; além disso, os asfaltenos C7I do P02 apresentam menor razão H/C, concordando que seriam mais aromáticos e propensos à precipitação. [33][34][35] Em relação aos heteroátomos (N, O e S), pesquisas indicam que estão concentrados nos asfaltenos e desempenham papel importante na autoassociação, pois normalmente fazem parte de suas porções polares, sítios em que ocorreriam ligações de hidrogênio e transferência de carga, interações envolvidas no processo de precipitação. 2,36 Neste trabalho foram avaliados os percentuais de oxigênio (O) e nitrogênio (N): ambos foram sempre maiores nos asfaltenos em relação aos maltenos correspondentes, concordando com resultados encontrados na literatura.…”
Section: Composição Elementar (Chno) Dos Petróleos E Frações C5 E C7 unclassified
“…2,36 Neste trabalho foram avaliados os percentuais de oxigênio (O) e nitrogênio (N): ambos foram sempre maiores nos asfaltenos em relação aos maltenos correspondentes, concordando com resultados encontrados na literatura. 2,33,34,36,37 Precipitação de asfaltenos nos petróleos pela adição de n-alcanos leves (nC < 4) e/ou dióxido de carbono Após os ensaios de caracterização inicial dos asfaltenos C5I e C7I dos petróleos P01 e P02, foram realizados experimentos em condições variadas de composição, temperatura e pressão. Foram adicionados metano e dióxido de carbono ao P01 (sistema P01+CH 4 +CO 2 , denominado S1) e somente propano ao P02 (sistema P02+C 3 H 8 , denominado S2).…”
Section: Composição Elementar (Chno) Dos Petróleos E Frações C5 E C7 unclassified
“…A comparison with NIR data showed that the mid-infrared spectra lead to a more reliable differentiation between the samples. In the context of crude oil characterization it is a common analytical task to determine the so-called saturate, aromatic, resin, asphaltenic (SARA) compounds [84][85][86]. For this purpose, FTIR and NIR are commonly employed in combination with multivariate data analysis.…”
Section: Petrochemical Liquid Fuelsmentioning
confidence: 99%